Pengembangan LKPD berbasis Pendekatan Saintifik berbantuan Liveworksheet pada Materi Gaya Kelas IV SD - Gandes Sekar Arum; Rohmatus Syafi’ah (Jurnal Simki Postgraduate, 2024)
This research is motivated by the lack of application of varied teaching materials in the independent curriculum at SD Negeri 4 Ngentrong. The teaching materials used still use smart agile books. This is the basis for researchers in developing LKPD based on a scientific approach with the help of a liveworksheet application on the material of style for grade IV. The aim is to develop and describe the validity of LKPD based on a scientific approach assisted by liveworksheets on the material of style. The method used in this study is Research and Development (R&D) with the 4-D model (Define, Design, Develop, Disseminate). The data collection technique used was a questionnaire, the data collection instrument used a questionnaire sheet for media experts, material experts, language experts, teacher responses, and student responses. The validity of the development of LKPD is determined from the results of validation by media experts, material experts and language experts, the results of the media expert assessment got an average percentage score of 88.75%, the results of the assessment from material experts got an average percentage score of 93%, and the results of the assessment from language experts got an average percentage score of 93.75%. The product development test to (practitioner) class teachers got a percentage score of 95% and the test to users (students) of class IV totaling 19 got a percentage score of 93.42%. So it can be concluded that LKPD based on a scientific approach assisted by liveworksheets is "very valid" and can be used in the learning process.